Bestiary : being an English version of the Bodleian Library, Oxford M.S. Bodley 764 : with all the original miniatures reproduced in facsimile /: being an English version of the Bodleian Library, Oxford M.S. Bodley 764 : with all the original miniatures reproduced in facsimile. (1993) - Unknown
No abstract available